What is "Equity"? Of Comparative Law, Time Travel and Judicial Cultures - Debruche, Anne-Françoise (Revue générale de droit, 2009)
What is "equity"? Does it mean the same as the word "équité" in French ? Can the word "equity", used in an English or an American legal text, be translated readily by équité without being misleading? The answer to those two last questions is no. In the language of the common law, "equity" means something very specific and much more complicated than what we have in mind when we say équité in our civil law traditions. The present paper, adapted from a lecture given in Brasilia, attempts to shed some light on this awkward subject, as it compares the notion of équité in the French civil law tradition with the concept of equity indigenous to the English common law tradition. The mode of presentation used is that of the imaginary time machine: specialists of équité are thus interviewed one by one (Montesquieu, Portalis, Justice Magnaud) in chronological order, followed by English judges associated with the development of equity (Lord Coke, Chancellor Ellesmere and Lord Denning), Those historical figures use examples borrowed from their own time in order to illustrate the workings of équité/equity: in France the principle of liability for things and the abuse of rights theory, in England the trust, the estoppel and the injunction. As a conclusion, we discover that equity does not necessarily mean fair, and that équité has to express itself indirectly under the guise of judicial interpretation.